2022
DOI: 10.1111/jam.15457
|View full text |Cite
|
Sign up to set email alerts
|

Postbiotics as potential promising tools for SARS-CoV-2 disease adjuvant therapy

Abstract: The SARS-CoV-2 pandemic defines the global health tension of our time. There are several continuous efforts to find a definitive cure in this regard. According to some adverse effects and problems of customary SARS-CoV-2 disease therapies, bioactive compounds, for example probiotics-derived metabolites (postbiotics) have been accomplishing supreme importance by investigators for adjuvant cures in patients with SARS-CoV-2. Postbiotics inhibit angiotensin-converting enzyme 2 activity and stimulate the immune sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 108 publications
0
4
0
Order By: Relevance
“…These data are available in both critical and non-critical patients [22,23]. In detail, whey-protein-rich formulas and pre-, pro-, and, lately, postbiotics have been used as add-on treatments for steroid, antibiotic, and antiviral therapy in COVID-19 subjects, with promising results [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…These data are available in both critical and non-critical patients [22,23]. In detail, whey-protein-rich formulas and pre-, pro-, and, lately, postbiotics have been used as add-on treatments for steroid, antibiotic, and antiviral therapy in COVID-19 subjects, with promising results [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…In order to change the immune system, the postbiotic substance primarily affects CD8+ T cells, interferon-gamma (IFN-γ), granulocyte phagocytic activity, tumor necrosis factor-alpha (TNF-α), proinflammatory cytokines, and elevated levels of IL-10 and IL-4 cytokines. The importance of microbial species, inactivation techniques, and an efficient postbiotic maintenance dose in delivery systems should be emphasized ( Khani et al, 2022 ). By creating the anti-inflammatory cytokine IL-10 in vitro utilizing L. reuteri 17,938, retinoic acid-driven mucosal-like dendritic cells have an impact on immunomodulation ( Aguilar-Toalá et al, 2018 ).…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Through its outstanding anti-inflammatory efficacy, postbiotics might lessen the severity of illnesses. Postbiotics also block a variety of proinflammatory signaling pathways to lessen cytokine storms ( Khani et al, 2022 ). Clinical research on the anti-inflammatory properties of the B. longum CECT-7347 strain of postbiotics revealed that they were successful in reducing gastrointestinal disturbance and acute inflammatory response as well as by activating the immunological pathways linked to a specific immune response ( Thorakkattu et al, 2022 ).…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…The en-FAEN þ en-PMLP controlled PV and acidity values, increased antioxidant activity and reduced microbial growth without any negative effects on sensory attributes, consequently leading to the increased shelf life of butter during 60 days of storage at 4°C. Khani et al (2023a) used metabolites derived from Lactobacillus strains as safe additives in the food industry. The postbiotics of L. plantarum showed an effective preservative to inhibit staphylococcus aureus in milk.…”
Section: Application Of Postbiotics In Foodmentioning
confidence: 99%